AUTHORITY AND FUNCTIONS OF PROSECUTORS IN INDONESIAN CRIMINAL JUSTICE - Ris Piere Handoko; Mhd Azhali Siregar; Muhammad Arif Sahlepi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Indonesia is a state based on law. The 1945 Constitution of the Republic of Indonesia, as amended 4th, as the constitution of the Unitary State of the Republic of Indonesia, is the highest positive law applicable in the Indonesian legal system. Discussing the Indonesian legal system means discussing the systemic law applicable in Indonesia. The criminal justice system contains a systemic movement of its supporting subsystems, namely the police, prosecutors, courts, and correctional institutions, which as a whole and constitute a unity (totality) strive to transform inputs into outputs that are the goal of the criminal justice system, namely, overcoming crime or controlling the occurrence of crime so that it is within the limits of tolerance that can be accepted by society. This study aims to determine the authority and function of prosecutors in the criminal justice system in Indonesia according to the Criminal Procedure Code. The method used in this study is the normative juridical method, namely the addition method by adhering to applicable legal norms or rules. The results of the study show: The prosecutor's office in Indonesia has quite limited authority compared to prosecutors in the Netherlands, England, or America. In addition to being listed in the Criminal Procedure Code, the duties and authorities of the prosecutor's office in carrying out its function as a subsystem/component of law enforcement of the Indonesian criminal justice system are listed in Law Number 16 of 2004 concerning the prosecutor's office. The prosecutor's office is a non-departmental institution, which means it is not under any ministry, the peak of the prosecutor's office leadership is held by the attorney general who is responsible to the president. The criminal justice process can be interpreted as all stages of examining criminal cases to uncover criminal acts that have occurred and take legal action against the perpetrators. By going through various institutions, the criminal justice process starts from the Police institution, continues to the Prosecutor's Office, to the Court Institution and ends at the Correctional Institution.